Pengaruh Media Short Education Movie Terhadap Pengetahuan Pencegahan TB Paru pada Keluarga Binaan Selama Pandemi Covid-19 di Desa Uteunkot Kota Lhokseumawe - Athaya, Alya; Zara, Noviana; Sahputri, Juwita (Jurnal Ilmiah Manusia Dan Kesehatan, 2025)
Pulmonary TB was an infectious disease that was still a health problem both in Indonesia and global, so, it was still one of the goals of sustainable health development. Indonesia at second place with the most pulmonary TB sufferers in the world. In 2023, pulmonary tuberculosis sufferers at Lhokseumawe City reached 833 cases, in a condition of Covid-19 pandemic, which can worsen the condition of pulmonary TB sufferers and people who were risk of being infected with pulmonary TB. Interesting health promotion could be done with short education film media, this media has advantages in displaying pictures, animations, and sounds. The purpose of this study was to find out how short education movie media influences knowledge of pulmonary TB prevention in assisted families during the Covid-19 pandemic. This study involved 51 respondents with quasi-experimental research type using one group pretest-posttest design. Data was collected using questionnaire sheet. The results showed that the characteristics of female respondents was more than male, with the majority being the late adolescent age group (17-25 years). The results showed an increase in knowledge of 100.0% in the good category after the intervention was carried out. The use of short education movie media has an influence on knowledge based on Wilcoxon test with p 0.000. The conclusion of this study was that, there is an influence of short education movie media on knowledge of pulmonary TB prevention in assisted families during the Covid-19 pandemic in Uteunkot village, Lhokseumawe City.